Alternativas de medición del "experienciar", de E. T. Gendlin - Peñas, Enrique Aguilar (Miscelánea Comillas, 2006)
The «experiencing» concept (Gendlin and Zimring, 1955; Gendlin, 1958, 1962) develops the process of symbolization of the felt meanings that are implicit in experiencing events. Gendlin relates experiencing to the therapeutic change. Klein, Mathieu, Gendlin and Kiesler (1969) developed the Experiencing Scale as a descriptive test. Based upon it, we elaborate the Experiencing Test («Test Experiencial», Aguilar, 2004), composed by ítems of incomplete sentences of multiple choice. We explored its factorial structure and relationship with the variables from EPQ-R test (Eysenck and Eysenck ([1985] 2001). Three factors are reported, no significant differences regarding age in the sample, but it does so regarding sex and neuroticism.